Synthesis of 100 Facet Dominant Anatase TiO2 Nanobelts and the Origin of Facet‐Dependent Photoreactivity. Issue 46 (26th September 2014) - Pan, Feng; Wu, Kai; Li, Hexing; Xu, Guoqin; Chen, Wei
Abstract Sword‐like anatase TiO2 nanobelts exposed with 78 % clean 100 facets were synthesized and the facet‐dependent photoreactivity of anatase TiO2 was investigated. By quantitative comparison with the reference 001 facets, the 100 facets possessed about ten‐times higher active sites density than that on 001 facets, resulting in higher photoreaction efficiency. After the active sites density normalization, the 100 and 001 facets exhibited distinct wavelength‐dependent photocatalytic performance, attributed to the anisotropic electronic structures in TiO2 crystals.